Peran Digital Governance dalam Peningkatan Daya Saing dan Branding Pariwisata Sumedang - Dadan Setia Nugraha (Universitas Medan Area, 2025)
This research aims to analyze the role of digital governance in increasing the competitiveness and branding of Sumedang tourism. Digital governance is seen as an important instrument in integrating information, technology, institutions, and socio-economic contexts in tourism promotion governance. This study uses a qualitative method with a naturalistic approach. The research method used is a qualitative method. Data was obtained through interviews, observations, and documentation of four informants determined by purposive sampling techniques, consisting of officials and staff of the Sumedang Regency Tourism, Culture, Youth, and Sports Office. Data analysis is carried out through reduction, presentation, and drawing of conclusions. The results show that the implementation of digital governance has supported the availability of accurate information, rapid data updates, and promotion through social media and virtual tours. However, its utilization is not optimal due to the limitations of digital infrastructure, human resource capacity, and the absence of standard operational standards in digital tourism promotion. The impact of digital promotion has been seen positively in improving the image of destinations and tourist interest in visits, even though the economic benefits have not been felt evenly. Overall, digital governance plays a strategic role in strengthening the branding and competitiveness of Sumedang tourism, noting the need to strengthen infrastructure, human resources, and more integrated policies.